Implementasi Kebijakan Perlindungan Anak dan Perempuan Korban Kekerasan pada Masa Pandemi Covid-19 di Kota Tangerang Selatan - Qumayratul Layliyah; Abdul Rahman; Mawar Mawar; Evi Satispi (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This study aims to determine and analyze the implementation of policies to protect children and women victims of violence during the Covid-19 pandemic in South Tangerang City. This research theory uses the theory of Policy Implementation in the Van Matter Van Horn concept with 6 (six) indicators including Policy Standard and Objectives, Resources, Inter-Organizational Communication, Characteristics of Implementers, Implementor Disposition, Social Environment, Economics and Politics. The research design used qualitative approach with a descriptive method. Methods of data collection by interview, observation and documentation. The results of the research found that the implementation of policies to protect children and women victims of violence has not yet been fully implemented. This is because there are still some findings of problems in policy implementation which include: lack of quantity of human resources, fragmentation originating from pressure from interest groups or from the legislative committee, lack of budget for policy implementation, lack of optimal support from DPRD and even the mayor in implementing child protection and women victims of violence, low commitment of policy implementers. Based on these conclusion points, this study recommends several things which include: increasing the number of staff implementing assistance in the UPTD P2TP2A South Tangerang city by 30-50 people, placing the protection of children and women victims of violence as a policy priority, re-activating social media and websites in order to facilitate socialization to the community as a whole, speed up the mentoring time to 7 days to 1 month, from 6 months to 2 years.